Evaluation of Serum Uric Acid, Glucose and Nitrite-Nitrate Levels in Ischemic Stroke Patients - Mohsen Hoseinian; Durdi Qujeq; Alijan Ahmadiahangar (Golestan University Of Medical Sciences, 2017)
Introduction: In this study, we evaluated serum levels of uric acid, nitrite-nitrate and glucose in ischemic stroke patients. Materials and Methods: The study was performed on 60 ischemic stroke patients admitted to the Rouhani Hospital in Babol and 60 healthy volunteers as controls. The subjects were matched in terms of age and gender. Uric acid and glucose levels were measured with standard biochemical kits. Level of nitrite-nitrate was evaluated by the Griess method. Data were analyzed with SPSS (version 19). Results: Serum uric acid, glucose and nitrite-nitrate levels were higher in ischemic stroke patients compared to healthy controls. However, these differences were not statistically significant (P>0.05). Conclusions: Serum uric acid, glucose and nitrite-nitrate levels are higher in ischemic stroke patients compared to healthy controls. Therefore, these factors could be used as useful markers for identification of elderly subjects at risk of ischemic stroke.